The Influence of Financial Performance and Service Performance on The Level of Financial Independence in The Vertical Hospital Under Ministry of Health - Dewi Astuti; Irvan Noormansyah; Lies Zulfiati (BPJP - STEI, 2021)
This study aims to test and analyze the effect of financial performance, Rentability Ratio, Liquidity Ratio and Activity and also service performance, Bed Occupancy Rate (BOR), Average Length Of Stay (AVLOS), Turn Over Interval (TOI), Bed Turn Over (BTO), Net Death Rate (NDR) dan Gross Death Rate (GDR) on financial of vertical hospitals under the Ministry of Health of The Republic of Indonesia which applies the public service agency financial management pattern for the period 2015-2018. This research uses quantitative research using secondary data on a population of 32 vertical hospitals under The Ministry of Health of The Republic of Indonesia which have the BLU status. Sample was determined by purposive sampling method, and get 10 hospitals with total observation are 40 observations. This research uses the documentation method through reports from The Directorate General of Treasury of BLU Financial Management, Ministry of Finance of the Republic of Indonesia, in the form of Government Performance Accountability Reports (LAKIP). This research uses descriptive statistical data analysis using panel data regression analysis. The result are financial performance and service performance simultaneously had a significant effect on the financial independence of the vertical BLU Hospitals. Partially only the Liquidity Ratio, Activity Ratio, AVLOS, BTO which have a positive and significant effect on hospital financial independence, while the Profitability Ratio, BOR, TOI, NDR, GDR variables have no significant effect on the level of hospital financial independence.